Determination of Chlorophyll-A and Total Suspended Sediment Using Airborne Remote Sensing Data - Jasni, Akmalhisham (2007)
The objective of this study are to derive the pattern of Chlorophyll-a (Chl-a) and Total Suspended Sediments (TSS) distribution as well as to built and integrate the Chl-a and TSS graphical models to a sub-system that can be utilized to generate the distribution maps of those parameters. The Chl-a and TSS modeling were generated from MASTER airborne data over the Kuala Terengganu coastal region. They were extracted by the empirical approach where the recorded reflectance of MASTER data was coincided to in situ data during the overpass. A linear coefficient of correlation R2 gained for Chl-a was 0.5839 from the band ratio of 1/2 and for TSS was 0.4382 from the band 8. This weak interaction was resulted due to the limited sampling points and restricted sea surface region in the study area. These models were then integrated into IMAGINE image processing software through an automated processing sub-system that was created to hold on Chl-a and TSS modeling.